網路時代資訊組織與Metadata課程發展 Curriculum Development on Organization of Information and Metadata in Internet Age - Mei-Ling Wang (Jiàoyù zīliào yǔ túshūguǎn xué, 2006)
編目作業向來是圖書館組織整理圖書文獻的重要機能，為了培育編目館員具備適當的知識技能，圖書資訊學系所普遍開設編目課程。近年來，由於資訊科技進步與網際網路盛行，對圖書館編目工作帶來重大衝擊，引發編目課程改名為資訊組織課程以及Metadata教育等議題。由於編目工作是圖書館的重要機能，使得資訊組織與Metadata課程探討更具意義。本論文首先回顧近十年相關的重要文獻，藉由美國臺灣經驗探索圖書館資訊組織工作的變革與需求，其次研析編目課程轉型成資訊組織課程的發展，涵蓋資訊組織教育原理、課程名稱、課程內涵與單元、基礎與進階課程安排、實習與作業，以及實驗課程。另一方面，由於數位圖書館大量建構與Metadata研究蓬勃，本論文也探討Metadata課程原理與設計，以及資訊組織與Metadata課程關係等議題。最後總結並提出資訊組織課程與Metadata課程未來發展建議。 As cataloging is one important library function, education for cataloging has been developed in library and information science (LIS) schools for more than one hundred years. Cataloging curricula are core components in LIS schools; however, information technologies and Internet bring a lot of changes. Cataloging curricula change into organization of information curricula and metadata curricula. The article mainly discusses influence factors and development of information organization curricula and metadata curricula in Internet Age. It made analysis of changing cataloging work form three perspectives including job changes, cataloger role change, and cataloger competencies change. New patterns of information organization curricula are explored, including theory, course title, course content, course structure, basic courses, advanced courses, field study and experimental design. Meanwhile, metadata curricula are also discussed. The study finally made discussion and suggestions.